Protection of Nrf2 against arsenite‐induced oxidative damage is regulated by the cyclic guanosine monophosphate‐protein kinase G signaling pathway. Issue 8 (24th October 2016) - Chen, Chengzhi; Jiang, Xuejun; Gu, Shiyan; Lai, Yanhao; Liu, Yuan; Zhang, Zunzhen
ABSTRACT: Arsenite has been shown to induce a variety of oxidative damage in mammalian cells. However, the mechanisms underlying cellular responses to its adverse effects remain unknown. We previously showed that the level of Nrf2, a nuclear transcription factor significantly increased in arsenite‐treated human bronchial epithelial (HBE) cells suggesting that Nrf2 is involved in responding to arsenite‐induced oxidative damage. To explore how Nrf2 can impact arsenite‐induced oxidative damage, in this study, we examined Nrf2 activation and its regulation upon cellular arsenite exposure as well as its effects on arsenite‐induced oxidative damage in HBE cells. We found that Nrf2 mRNA and protein levels were significantly increased by arsenite in a dose‐ and time‐dependent manner. Furthermore, we showed that over‐expression of Nrf2 significantly reduced the level of arsenite‐induced oxidative damage in HBE cells including DNA damage, chromosomal breakage, lipid peroxidation and depletion of antioxidants. This indicates a protective role of Nrf2 against arsenite toxicity. This was further supported by the fact that activation of Nrf2 by its agonists, tertiary butylhydroquinone (t‐BHQ) and sulforaphane (SFN) resulted in the same protective effects against arsenite toxicity. Moreover, we demonstrated that arsenite‐induced activation of Nrf2 was mediated by the cyclic guanosine monophosphate (cGMP)‐protein kinase G (PKG) signaling pathway. This is the first evidence showing that Nrf2 protects against arsenite‐induced oxidative damage through the cGMP‐PKG pathway. Our study suggests that activation of Nrf2 through the cGMP‐PKG signaling pathway in HBE cells may be developed as a new strategy for prevention of arsenite toxicity. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 2004–2020, 2017.